Methylation of three genes encoded by X chromosome in blood leukocytes and colorectal cancer risk. (18th June 2021) - Tian, Tian; Bi, Haoran; Zhang, Ding; Liu, Yupeng; Sun, Hongru; Jia, Chenyang; Zheng, Ting; Huang, Hao; Fu, Jinming; Zhu, Lin; Zhao, Yashuang
Abstract: X chromosome change has been proved to be associated with carcinogenesis and related to gender differences in cancer risk. If aberrant methylation of genes encoded by X chromosome involve in the risk and prognosis of cancers, including colorectal cancer (CRC), remain unclear. We conducted a case–control study consisted of 432 CRC cases and 434 controls, detecting the methylation levels of FAM156B, PIH1D3, and PPP1R3F in the X chromosome in blood leukocytes using methylation‐sensitive high‐resolution melting (MS‐HRM). We analyzed the relationship between the methylation levels and CRC susceptibility and then explored the interactions with environmental factors on CRC risk with logistics regression. Moreover, we conducted a follow‐up study containing 225 CRC patients to explore the associations between the methylation of FAM156B, PPP1R3F, and PIH1D3 and CRC prognosis. The hypermethylation of FAM156B, PPP1R3F, and PIH1D3 was related to increased CRC risk (ORPS‐adj = 2.932, 95% confidence interval [CI]: 2.029–4.237; ORPS‐adj = 1.602, 95% CI: 1.078–2.382; ORPS‐adj = 1.628, 95% CI: 1.065–2.490, respectively). In the multiple CpG site methylation (MCSM) analysis, compared with non‐MCSM, a significant relationship between MCSM and increased CRC risk was found (ORPS‐adj = 2.202, 95% CI: 1.512–3.208). We observed synergistic interaction between PPP1R3F hypermethylation and fried food consumption on CRC risk (ORi = 2.682, 95% CI: 1.321–5.446). However, there were no associations between the methylation of FAM156B, PPP1R3F, and PIH1D3 and CRC prognosis ( p > 0.05). In conclusion, the methylation of FAM156B, PPP1R3F, and PIH1D3 genes in blood leukocytes is significantly related to CRC risk and may be potential biomarkers for CRC risk but not prognosis. Abstract : Our results showed that the methylation of FAM156B, PPP1R3F, and PIH1D3 genes in blood leukocytes is significantly associated with colorectal cancer (CRC) risk and may be potential biomarkers for CRC risk.